Urine osmolality and conductivity as indices of hydration status in athletes in the heat - Shirreffs, S. M.; Maughan, R. J. (Medicine & Science in Sports & Exercise, 1998)
PURPOSE: The purpose of this study was to determine a quick and easy method for assessment of day-to-day hydration status in athletes in the heat. METHODS: Measurement of the osmolality of the first urine sample of the day collected after wakening but before breakfast established a standardized collection procedure to allow day-to-day comparisons of individuals. RESULTS: Laboratory measurements established that a difference in osmolality is found when individuals are dehydrated by a moderate extent in comparison with an euhydrated situation: the osmolality of the first morning urine sample of control subjects (N = 11) averaged over 5 d was 675 (+/- 232) mosmol.kg-1 (mean +/- SD). For subjects who were hypohydrated by exercise followed by fluid restriction, morning urine osmolality was 924 (+/- 99) mosmol.kg-1 (P < 0.001, N = 11, averaged over 7 d). Field measurements from 29 athletes undertaking warm weather training indicated that the athletes could, with appropriate feedback, maintain a satisfactory hydration status. Athletes in weight category sports tended to record a higher morning urine osmolality, reflecting their attempts to dehydrate: recorded values were 627 (+/- 186) mosmol.kg-1 (nonweight category sports, N = 8), 775 (+/- 263) mosmol.kg-1 (boxers, N = 15) and 777 (+/- 254) mosmol.kg-1 (wrestlers, N = 6). Results obtained with a hand-held portable conductivity were compared with those from measured osmolality. CONCLUSIONS: The findings suggest that such an instrument could provide athletes with reliable information as to their hydration status from measurement of the first morning urine of the day and therefore provide a quick and easy method for achieving an approximation of hydration status from day-to-day.